The role of mosquito surveillance in monitoring arboviral infections in Croatia : Uloga praćenja komaraca u kontroli arbovirusnih infekcija u Hrvatskoj - Janev Holcer, Nataša (Array, 2020)
In accordance with the noticed growing trend in the number of vector-borne disease cases, the extent of public health significance of this problem is also increasing. However, the strengthening of capacities for suppression of these outbreaks is present. With the aim of protecting population from arbovirus infections, there is a need for continuous monitoring and evaluation of risk factors related to vectors and vector borne diseases and human health, for which data is acquired through monitoring programs. In order to address these issues, several activities must be integrated and taken into consideration: vector surveillance, entomological activity, early detection system, preventive measures, counter-epidemic measures and virus detection in vectors, reservoirs or infected animals. There is a legal framework regarding mosquito monitoring on a local, as well as national level. Additionally, at the initiative of the Croatian Institute of Public Health, invasive mosquito species monitoring is being implemented and continuously conducted since 2016.